Identification and Attenuation of Barriers to Entrepreneurship: Targeting New Destination Latino Migrants. (February 2014) - Moon, Zola K.; Farmer, Frank L; Miller, Wayne P.; Abreo, Christina
Results are reported from a Latino immigrant entrepreneur needs assessment survey. The research project was conducted to identify barriers to business formation and continuation within the target population. A total of 171 surveys representing more than 200 businesses from 39 communities in 21 counties in western Arkansas were collected. Nearly 42% of respondents cited start-up capital as their biggest barrier with another 15% naming it as the second biggest barrier. Understanding government regulations and tax information rated as the second biggest barrier that Latinos encountered. This barrier is more pronounced in rural areas than in urban areas. Other top concerns include advertising, location, and obtaining licenses and permits. A closer examination of barriers finds nuanced differences between rural and urban entrepreneurs. Outreach programs and materials developed in response to research findings are presented.